Peningkatan Hasil Pembelajaran TematikTerpadu dengan Menggunakan Model Discovery Learning (DL) di kelas V SDN 114/III Dusun Baru Siulak Sungai Penuh Kerinci - Sari, Indah Ririn Kurnia (Universitas Negeri Padang, 2021)
This research is motivated by the less optimal integrated thematic learning that results in students not understanding the material so that it impacts on learning outcomes. This study aims to describe the Improvement of Integrated Thematic Learning Outcomes Using the Discovery Learning Model in Class V Students of SDN 114 / III Baru Siulak Sungai Penuh Kerinci. This type of research is PTK with qualitative and quantitative approaches. Research data in the form of observations, tests and non-tests. The study was conducted in two cycles. The research subjects were teachers and class V students. The results showed in the first cycle RPP an average of 83.3% (good), increased in the second cycle to 94.44% (excellent). The implementation of learning aspects of the first cycle teacher on average 84.37% (good), increased in the second cycle to 93.75% (excellent). Aspects of the first cycle students on average 84.37% (good) increased in the second cycle to 93.75% (excellent). Learning outcomes in the first cycle obtained an average of 83.33% (good) and increased in the second cycle with an average value of 94.44% (excellent).